Factors of Attractiveness Influencing Consumers’ Decisions to Purchase Vivo Smartphones at Sunrise Cellular Bireuen - Zuriani Ritonga; Rauzana Rauzana; Sri Murniyanti; Nafsiah Suhaila; Munawarah Munawarah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The purpose of this study was to determine and explain whether the factors of product attractiveness affect consumer purchasing decisions to buy smartphones Vivoat Sunrise Cellular Bireuen. The author draws the hypothesis that there are several factors, namely product quality, product variety and product features that influence consumer decisions to buy smartphones Vivo. The population in this study are consumers who buy smartphones Vivoat Sunrise Cellular Bireuen. The sampling technique in this study used random sampling (randomly) as many as 60 respondents, the data collection techniques used were questionnaires, literature studies, and interviews. The instrument test in this study uses multiple linear regression test, classical assumption test, t test, f test, and coefficient of determination with sig level. (α) 0.05 data analysis using software statistical data processingSPSS version 23.0 for windows. The results of this study found that product quality, product variety, and product features had a significant effect overall. The value of the coefficient of determination obtained R2= 0.495 concluded that 49.5% of consumer purchasing decisions are influenced by product quality, product variations, and product features, while the remaining 50.5% is influenced by other variables not examined.